PENGARUH PENYULUHAN TENTANG PIJAT BAYI TERHADAP PERILAKU IBU DALAM MELAKUKAN PIJAT BAYI SECARA MANDIRI - Rohmah, Dina Mustika; Aryaneta, Yenni (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2020)
The information on benefits of clinical baby massage is not well-spread among our general society. More often than not, many still relegate the baby massage job to a witchdoctor because of lack of awareness of instead trusting the practice in the hand of medical professionals. A mother must be well-educated in doing the baby massage practice before she can later self-perform the job. This research aims to discover the impact of advocating clinical baby massage on the motherâ€™s conduct in self-performing the practice. The research employs pre-experimental design with pretest and posttest one group setting. It took place in BPM (independent practice midwife) Walladatun Islah. The sample population is the mothers visiting the BPM for vaccination. Data collecting technique employs total sampling involving 30 respondents. Data collecting instruments are leaflets and video for independent variable, and observation sheet by check-listing for dependent variable. Data analyzing technique employs paired sample t-test. The findings reveal that from the bivariate test using Kolgomorov-Smirnov method, out of 30 respondents, significant Ï-value = 0.200 > 0.05 indicates both variablesâ€™ distributions are normal to proceed to the t-test. The value from both pretest and posttest is 16.603 with significance level of 0.000, indicating it is bigger than t-table (16.603 > 2.045) therefore the hypothesis of the research is tolerable. In conclusion, there is a strong relevance between the advocacy of practicing clinical baby massage and the motherâ€™s conduct in self-performing the job. In suggestion, healthcare workers and professionals are expected to be more active in advocating both pregnant and postpartum women the benefits of clinical baby massage for example during the antenatal care class or visit.